Benefit of actively mixing prey in a plant‐inhabiting predatory mite. (8th September 2021) - Marques, Renata V.; Sarmento, Renato A.; Pallini, Angelo; Oliveira, Adriana G.; Ferreira, Dara E. S.; Janssen, Arne
Abstract : 1. Many animals can actively redress nutrient imbalances in their diet to maximise performance. However, food items are commonly patchily distributed in nature, thus, animals often need to commute between prey patches to mix their diet. 2. We previously found that females of two species of predatory mites showed a higher oviposition rate when feeding on a mixture of eggs of co‐occurring phytophagous mites than on each prey separately. Besides, they searched for such a prey mixture on artificial arenas. 3. In nature, however, the two prey species are found on different parts of their host plant; hence, the predators need to commute between plant parts to obtain a mixed diet. 4. Here, we show that the reproduction of one of these predators was highest on mixtures consisting of various proportions of these prey, and was lower on single diets and on a mixture with a high proportion of one of the two prey. The predators consumed prey eggs in proportions differing from those offered, suggesting that they actively selected prey to obtain a mixed diet. 5. We found that the oviposition of the predator was lower on plants inoculated with either of the two prey species alone than on plants on which the eggs of the two prey species occurred on separate leaves of the same plant, forcing the predators to commute between the two prey. 6. We conclude that the predators actively searched for a mixed diet consisting of prey that were spatially separated on a plant. Abstract : Predators consumed two prey species in proportions differing from those offered. Predators actively selected a mixed diet, also on intact plants. This resulted in increased predator reproduction.